A predictive framework for the reproducible seed-mediated synthesis and functionalization of gold nanorods - Brian Novati; Lucia Salvioni; Melissa Saibene; Alessandro Colombo; Roberto Lorenzi; Angelo Monguzzi; Stefania Garbujo; Miriam Colombo; Marco D. Giustra; Davide Prosperi (Chemical Engineering Journal, 2026)

Bubble-mediated printability optimization in chemically foamed metakaolin-based geopolymer inks: Mechanism and enhanced adsorption - Xuhao Zhang; Kai Huang; Marco D'Agostini; Xiao Zhang; Minghui Ma; Paolo Colombo (Applied Clay Science, 2026)

Novel extruded 3D printed potassium geopolymer composites containing chitosan - Angelo Oliveira Silva; Marco D'Agostini; Dachamir Hotza; Paolo Colombo (Applied Clay Science, 2026)

Design of 3D-printed hydroxyapatite intervertebral fusion cages in a patient specific framework - Anna De Cet; Martina Colombo; Luca D’Andrea; Ilaria Rota; Luigi La Barbera; Pasquale Vena; Dario Gastaldi (Medical & Biological Engineering & Computing, 2026)
Fusion surgery involves replacing degenerated intervertebral discs with artificial implants, usually composed of titanium alloys or PEEK, requiring bone grafting to assist tissue growth. This study aims to evaluate numerically 3D-printed porous ceramic implants as a bioactive alternative. Clinical computed tomographies of an adult patient were used to reconstruct the geometry and to assign mechanical properties to L1 and L2 vertebrae, utilizing a patient-specific anisotropic micromechanics-based model. The influence of different microstructural choices on a porous hydroxyapatite-based scaffold was analysed through finite element analysis, simulating standing and flexion. The analyzed scaffolds included: microstructured Face Centered Cubic (FCC) and Kelvin-based devices with uniform porosity (75%), and a Voronoi microstructured scaffold with uniform (75%) and graded porosity (60% external, 90% internal). Homogenized models were considered as a potential strategy to reduce computational costs. The FCC geometry and graded Voronoi proved more mechanically resistant to failure. Homogenized mechanical properties simplified the model, but didn’t accurately represent microstructural behaviour and local mechanical failure couldn’t be suitably identified. Patient-specific models allowed for a more accurate representation of mechanical stresses, leading to a reduced risk of structural failure. Hydroxyapatite proves to be a promising material for 3D-printed lumbar interbody fusion cages, able to provide primary stability.

Conversion of municipal biowaste into value-added products toward a circular bioeconomy: bridging the gap between laboratory-scale and full-scale implementation - José Manuel Alejandro Cerdán; Tatiana Kimura Kodama; G. H. D. Oliveira; Lucas Tadeu Fuess; Júlia Fonseca Colombo Andrade; Aldo Roberto Ometto (Clean Technologies and Environmental Policy, 2026)
Scaling-up municipal biowaste conversion technologies to industrial levels is essential for advancing clean and sustainable technologies and addressing significant technical, economic, and environmental challenges associated with urban organic waste management. Studies that explore technological gaps across the upstream, midstream, and downstream processing stages of biorefineries are critical for transforming biowaste into value-added products. This study aims to fill these gaps through a systematic literature review following the PRISMA guidelines and utilizing the Technology Readiness Level (TRL), which enabled the selection of 88 cases subsequently analyzed using descriptive and content analysis. The main findings show that anaerobic digestion has achieved full commercial maturity (TRL 9), while acidogenic fermentation remains mostly at TRL 6–7, and other pathways such as microbial protein or holocellulase production are still at early stages (TRL 3–4). High-value products, including polyhydroxyalkanoates (PHA) and succinic acid, are clustered at TRL 6–7, typically demonstrated at pilot scale, whereas hydrochar from hydrothermal carbonization has progressed up to TRL 8–9. Companies and projects confirm the feasibility of integrating biological, chemical, and thermal pathways into biorefineries, spanning a wide range of TRLs and showcasing their potential within the circular bioeconomy. Key gaps persist in scaling downstream processes for product purification, reducing costs, addressing feedstock variability, and optimizing pretreatment. By synthesizing experimental evidence with industrial demonstrations and sustainability assessments, this study provides a comprehensive perspective on how municipal biowaste can be converted into both non-fuel bioproducts and biofuels, thereby supporting circular bioeconomy strategies for future environmental policies. Graphical Abstract

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Effects of two natural astaxanthin products derived from the green microalga Haematococcus lacustris on production parameters and fillet quality of Atlantic salmon (Salmo salar) - Juan A. Manríquez-Hernández; Sean M. Tibbetts; Mark D. Fast; Stacey R. Goldberg; Roumiana Stefanova; Stefanie M. Colombo (Aquaculture International, 2025)

P32-19 Absorption Test on Different Formulations of Medical Devices Containing Silver Sulfadiazine - M. Mori; D. Colombo; A. Zerboni; D. Ianev; S. Stoilova (Toxicology Letters, 2025)

P16-06 Evaluation of the Mechanism of Action and Immunomodulatory Properties of an Oral Medical Device Containing Gelatin Tannate and Tyndallized Bacteria - A. Zerboni; S. Stoilova; D. Colombo; M. Mori (Toxicology Letters, 2025)

One Health approach and tiered strategy to assess anticoagulant rodenticides exposure in red foxes (Vulpes vulpes) from Central Italy - Rachele Rocchi; Federica Castellani; Romolo Salini; Stefania Salucci; Elga Ersilia Tieri; Giampiero Scortichini; Susanna Tora; Antonio Coccaro; Antonio Cocco; Mariasole Colombo; Alice Menozzi; Marcos Pérez López; et al. (Environmental Pollution, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Valorization of corn stover in a single experimental unit: The synergistic effects of steam explosion and semi-continuous subcritical water processing - Francisco D. Vezaro; Suelly R. Hollas; Fernanda A. Colombo; Alex Schulz; Crisleine P. Draszewski; Fernanda de Castilhos; Ederson R. Abaide; Flávio D. Mayer (Science of The Total Environment, 2025)

Factors controlling the water quality of rock glacier springs in European and American mountain ranges - Stefano Brighenti; Nicola Colombo; Thomas Wagner; Michael Pettauer; Nicolas Guyennon; Karl Krainer; Monica Tolotti; Michela Rogora; Luca Paro; Sandra M. Steingruber; Chantal Del Siro; Cristian Scapozza; et al. (Science of The Total Environment, 2024)

Low prevalence of microplastic contamination in the bottom sediments and deep-sea waters of the Bransfield strait, Antarctica - Gabriel Enrique De-la-Torre; Ana D. Forero López; Carolina V. Colombo; Guido N. Rimondino; Fabio E. Malanca; Martha Barahona; Luis Santillán (Chemosphere, 2024)

LP-38 DockTox: a molecular docking platform for screening small molecules targeting Molecular Initiating Events (MIEs) relevant to liver, kidney and brain adverse events - R. Ortega Vallbona; D. Talavera Cortés; L.E. Carpio Mulas; E. Colombo; A. Roncaglioni; M. Garcia de Lomana; E. Benfenati; D. Gadaleta; R. Gozalbes; E. Serrano Candelas (Toxicology Letters, 2024)

An aquaculture risk model to understand the causes and consequences of Atlantic Salmon mass mortality events: A review - Zaman Sajid; A. Kurt Gamperl; Christopher C. Parrish; Stefanie M. Colombo; Javier Santander; Charles Mather; Barbara Neis; Ingunn Marie Holmen; Ramón Filgueira; Cynthia H. McKenzie; Lissandra Souto Cavalli; Mohamed Jeebhay; et al. (Reviews in Aquaculture, 2024)
Mass mortality events (MMEs) are defined as the death of large numbers of fish over a short period of time. These events can result in catastrophic losses to the Atlantic salmon aquaculture industry and the local economy. However, they are challenging to understand because of their relative infrequency and the high number of potential factors involved. As a result, the causes and consequences of MMEs in Atlantic salmon aquaculture are not well understood. In this study, we developed a structural network of causal risk factors for MMEs for aquaculture and the communities that depend on Atlantic salmon aquaculture. Using the Interpretive Structural Modeling (ISM) technique, we analysed the causes of Atlantic salmon mass mortalities due to environmental (abiotic), biological (biotic) and nutritional risk factors. The consequences of MMEs were also assessed for the occupational health and safety of aquaculture workers and their implications for the livelihoods of local communities. This structural network deepens our understanding of MMEs and points to management actions and interventions that can help mitigate mass mortalities. MMEs are typically not the result of a single risk factor but are caused by the systematic interaction of risk factors related to the environment, fish diseases, feeding/nutrition and cage‐site management. Results also indicate that considerations of health and safety risk, through pre‐ and post‐event risk assessments, may help to minimize workplace injuries and eliminate potential risks of human fatalities. Company and government‐assisted socio‐economic measures could help mitigate post‐mass mortality impacts. Appropriate and timely management actions may help reduce MMEs at Atlantic salmon cage sites and minimize the physical and social vulnerabilities of workers and local communities.

The impact of behavioural weight management interventions on eating behaviour traits in children with overweight or obesity: systematic review and meta-analysis - Patricia Eustachio Colombo; Milindu Wickramarachchi; Aiswarya Lakshmi; Laura Kudlek; Amy Ahern; Struan Tait; Natasha Reid; Rebecca A. Jones; Andrea D. Smith (Appetite, 2024)

Influence of the geographic location and house characteristics on the concentration of microplastics in indoor dust - Lorgio Valdiviezo-Gonzales; Paola Ortiz Ojeda; Dante Espinoza Morriberón; Carolina V. Colombo; Guido Noé Rimondino; Ana D. Forero López; Melisa D. Fernández Severini; Fabio Ernesto Malanca; Gabriel Enrique De-la-Torre (Science of The Total Environment, 2024)

High-Resolution In Situ Characterization of the Hydrochemical Variability Along the Fluvio-marine Transition of the Río de la Plata Estuary, Argentina - S. Heguilor; E. D. Speranza; L. M. Tatone; C. N. Skorupka; M. C. Migoya; J. C. Colombo (Estuaries and Coasts, 2024)

Marine microdebris pollution in sediments from three environmental coastal areas in the southwestern Argentine Atlantic - A.D. Forero-López; M.A. Toniolo; C.V. Colombo; G.N. Rimondino; D. Cuadrado; G.M.E. Perillo; F.E. Malanca (Science of The Total Environment, 2024)

High-resolution temporal variations of nitrate in a high-elevation pond in alpine tundra (NW Italian Alps) - N. Colombo; R. Balestrini; D. Godone; D. Vione; D. Said-Pullicino; G. Viviano; M. Martin; C.A. Delconte; S. Fratianni; A.G. Capodaglio; E. Pintaldi; M. Freppaz; et al. (CATENA, 2024)

Hymenopteran parasitoids of black soldier fly Hermetia illucens (L.) (Diptera: Stratiomyidae) in chicken farms with two new species from India - C. Binoy; Gérard Delvare; Wesley D. Colombo; K.S. Surya; P.M. Sureshan (Journal of Asia-Pacific Entomology, 2023)

Calorimetric determination of wet snow liquid water content: The effect of test conditions on the calorimeter constant and its impact on the measurement uncertainty - D. Fasani; F. Cernuschi; L.P.M. Colombo (Cold Regions Science and Technology, 2023)

Insights into the systematics of Afrotropical Laelius (Hymenoptera, Bethylidae): combining molecular and morphological data to associate dimorphic species - Wilson J. Marques; Wesley D. Colombo; Celso O. Azevedo (Zoologischer Anzeiger, 2023)

OS04-02: Next Generation PBK modeling with PK-Sim for the prediction of chemical distribution in humans - R. Geci; D. Gadaleta; S. Proença; E. Colombo; M. García de Lomana; R. Ortega Vallbona; N. Kramer; A. Paini; L. Küpfer; S. Schaller (Toxicology Letters, 2023)

Aerial insectivorous bat responses to 30 years of forest insularization in a dam-created Amazonian archipelagic landscape - Raffaello Di Ponzio; Guthieri Teixeira Colombo; Thiago Bicudo; Maíra Benchimol; Maria João Ramos Pereira; Carlos A. Peres; Paulo Estefano D. Bobrowiec (Biological Conservation, 2023)

Modeling the compressive strength of metakaolin-based geopolymers based on the statistical analysis of experimental data - M. Muracchioli; G. Menardi; M. D' Agostini; G. Franchin; P. Colombo (Applied Clay Science, 2023)

Psilocybin prevents reinstatement of alcohol seeking by disrupting the reconsolidation of alcohol-related memories - F. Benvenuti; D. Colombo; L. Soverchia; N. Cannella; E. Domi; R. Ciccocioppo (Psychopharmacology, 2023)

Study of the mechanical properties of thermoplastic polyurethane (TPU) recycled from end-of-life ski-boots and techno-economic analysis (TEA) of the mechanical recycling processes - A. Nanni; L. Crosetta; G. La Fauci; F. Biagi; M. Parisi; D. Colombo; M. Colonna (Sustainable Chemistry and Pharmacy, 2023)

: A high-order discontinuous Galerkin solver for flow simulations and multi-physics applications - E. Ferrer; G. Rubio; G. Ntoukas; W. Laskowski; O.A. Mariño; S. Colombo; A. Mateo-Gabín; H. Marbona; F. Manrique de Lara; D. Huergo; J. Manzanero; A.M. Rueda-Ramírez; et al. (Computer Physics Communications, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Molecular Identification and Antimicrobial Activity of Foliar Endophytic Fungi on the Brazilian Pepper Tree (Schinus terebinthifolius) Reveal New Species of Diaporthe - Germana D. dos Santos; Renata R. Gomes; Rosana Gonçalves; Gheniffer Fornari; Beatriz H. L. N. S. Maia; Claudia Schmidt-Dannert; Francois Gaascht; Chirlei Glienke; Gabriela X. Schneider; Israella R. Colombo; Juliana Degenhardt-Goldbach; João L. M. Pietsch; et al. (Current Microbiology, 2021)

Gulliver’s virtual travels: active embodiment in extreme body sizes for modulating our body representations - S. Serino; F. Scarpina; A. Chirico; A. Dakanalis; D. Di Lernia; D. Colombo; V. Catallo; E. Pedroli; G. Riva (Cognitive Processing, 2020)
It is noted that the perceptual experience of body and space can be modulated by changing the action capabilities or by manipulating the perceived body dimensions through a multisensory stimulation. This study adds to pre-existing literature by investigating the alterations in bodily experience following embodiment to both enlarged and shrunked bodies, while participants actively navigated in a virtual environment. A normal-sized body served as a reference condition. After each embodied navigation, participants estimated the height and width of three different body parts. Results revealed that the embodiment over shrunked body induced a significant reduction in participants’ body image, while no changes were reported after the embodiment over the enlarged body. Findings were discussed in terms of previous literature exploring the constraints implicated in the ownership over different bodies.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

In S. cerevisiae hydroxycitric acid antagonizes chronological aging and apoptosis regardless of citrate lyase - Maurizio D. Baroni; Sonia Colombo; Olivier Libens; Rani Pallavi; Marco Giorgio; Enzo Martegani (Apoptosis, 2020)
Caloric restriction mimetics (CRMs) are promising molecules to prevent age-related diseases as they activate pathways driven by a true caloric restriction. Hydroxycitric acid (HCA) is considered a bona fide CRM since it depletes acetyl-CoA pools by acting as a competitive inhibitor of ATP citrate lyase (ACLY), ultimately repressing protein acetylation and promoting autophagy. Importantly, it can reduce inflammation and tumour development. In order to identify phenotypically relevant new HCA targets we have investigated HCA effects in Saccharomyces cerevisiae , where ACLY is lacking. Strikingly, the drug revealed a powerful anti-aging effect, another property proposed to mark bona fide CRMs. Chronological life span (CLS) extension but also resistance to acetic acid of HCA treated cells were associated to repression of cell apoptosis and necrosis. HCA also largely prevented cell deaths caused by a severe oxidative stress. The molecule could act widely by negatively modulating cell metabolism, similarly to citrate. Indeed, it inhibited both growth reactivation and the oxygen consumption rate of yeast cells in stationary phase. Genetic analyses on yeast CLS mutants indicated that part of the HCA effects can be sensed by Sch9 and Ras2, two conserved key regulators of nutritional and stress signal pathways of primary importance. Our data together with published biochemical analyses indicate that HCA may act with multiple mechanisms together with ACLY repression and allowed us to propose an integrated mechanistic model as a basis for future investigations.

Reduction of hippocampal IL-6 levels in LPS-injected rats following acute exendin-4 treatment - Luiza P. Géa; Eduarda D. da Rosa; Bruna S. Panizzutti; Érica Z. de Aguiar; Larissa F. de Oliveira; Pamela Ferrari; Angelo Piato; Rosane Gomez; Rafael Colombo; Adriane R. Rosa (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Coupled Modeling of Sedimentary Basin and Geomechanics: A Modified Drucker–Prager Cap Model to Describe Rock Compaction in Tectonic Context - N. Guy; D. Colombo; J. Frey; T. Cornu; M. C. Cacas-Stentz (Rock Mechanics and Rock Engineering, 2019)

High export of nitrogen and dissolved organic carbon from an Alpine glacier (Indren Glacier, NW Italian Alps) - Nicola Colombo; Daniele Bocchiola; Maria Martin; Gabriele Confortola; Franco Salerno; Danilo Godone; Michele Eugenio D’Amico; Michele Freppaz (Aquatic Sciences, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Irrigation distribution uniformity analysis on a lateral-move irrigation system - Lessandro Coll Faria; Bernardo Gomes Nörenberg; Alberto Colombo; Michael D. Dukes; Luis Carlos Timm; Samuel Beskow; Tamara Leitzke Caldeira (Irrigation Science, 2019)

Exploring by whole exome sequencing patients with initial diagnosis of Rubinstein–Taybi syndrome: the interconnections of epigenetic machinery disorders - Gloria Negri; Pamela Magini; Donatella Milani; Milena Crippa; Elisa Biamino; Maria Piccione; Stefano Sotgiu; Chiara Perrìa; Giuseppina Vitiello; Marina Frontali; Antonella Boni; Elisabetta Di Fede; et al. (Human Genetics, 2019)

Variability of sun‐induced chlorophyll fluorescence according to stand age‐related processes in a managed loblolly pine forest - Roberto Colombo; Marco Celesti; Remo Bianchi; Petya K. E. Campbell; Sergio Cogliati; Bruce D. Cook; Lawrence A. Corp; Alexander Damm; Jean‐Christophe Domec; Luis Guanter; Tommaso Julitta; Elizabeth M. Middleton; et al. (Global Change Biology, 2018)
Leaf fluorescence can be used to track plant development and stress, and is considered the most direct measurement of photosynthetic activity available from remote sensing techniques. Red and far‐red sun‐induced chlorophyll fluorescence ( SIF ) maps were generated from high spatial resolution images collected with the HyPlant airborne spectrometer over even‐aged loblolly pine plantations in North Carolina (United States). Canopy fluorescence yield (i.e., the fluorescence flux normalized by the light absorbed) in the red and far‐red peaks was computed. This quantifies the fluorescence emission efficiencies that are more directly linked to canopy function compared to SIF radiances. Fluorescence fluxes and yields were investigated in relation to tree age to infer new insights on the potential of those measurements in better describing ecosystem processes. The results showed that red fluorescence yield varies with stand age. Young stands exhibited a nearly twofold higher red fluorescence yield than mature forest plantations, while the far‐red fluorescence yield remained constant. We interpreted this finding in a context of photosynthetic stomatal limitation in aging loblolly pine stands. Current and future satellite missions provide global datasets of SIF at coarse spatial resolution, resulting in intrapixel mixture effects, which could be a confounding factor for fluorescence signal interpretation. To mitigate this effect, we propose a surrogate of the fluorescence yield, namely the Canopy Cover Fluorescence Index ( CCFI ) that accounts for the spatial variability in canopy structure by exploiting the vegetation fractional cover. It was found that spatial aggregation tended to mask the effective relationships, while the CCFI was still able to maintain this link. This study is a first attempt in interpreting the fluorescence variability in aging forest stands and it may open new perspectives in understanding long‐term forest dynamics in response to future climatic conditions from remote sensing of SIF .

Beneficial and Safety Properties of a Corynebacterium vitaeruminis Strain Isolated from the Cow Rumen - M. Colombo; N. P. A. Castilho; S. D. Todorov; L. A. Nero (Probiotics and Antimicrobial Proteins, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

Fatty acid alterations in the detritivorous Prochilodus lineatus promoted by opportunistic feeding on sewage discharges in the R ío de la P lata estuary - E. D. Speranza; M. Colombo; L. M. Tatone; N. Cappelletti; M. C. Migoya; J. C. Colombo (Journal of Fish Biology, 2016)
Muscle fatty acid profiles and PCB contents of the detritivorous species Prochilodus lineatus and its diet (stomach contents, settling particles and sediments) were analysed from reference and polluted areas of the Paraná‐Rio de la Plata basin, to evaluate the alterations produced by opportunistic feeding on sewage discharges. Overall muscle fatty acid composition was dominated by saturated and monounsaturated 16 and 18 carbon (18 C‐ FA ) components with reduced long‐chain polyunsaturated fatty acids ( LC‐PUFA ). Compared to sediments, settling particles and stomach contents were enriched in lipids and had a similar fatty acid composition. Opportunistic feeding on sewage detritus at Buenos Aires resulted in enhanced PCB and triglyceride accumulation, with higher proportions of 18 C‐ FA and lower proportions of 16:1 and LC‐PUFA compared to fish from northern pristine reaches of the basin. Mid‐Paraná showed intermediate values reflecting mixing of the North stock with migrating Buenos Aires P. lineatus identified by their lipid and contaminant profile. According to multivariate analyses, this geographical variation of fatty acid composition was strongly influenced by PCB concentration. Prochilodus lineatus assimilates the energy subsidy of sewage inputs through enhanced lipogenesis with dominant 18 C‐ FA and significant amounts of valuable LC‐PUFA . This lipid alteration facilitates the bioaccumulation of PCBs which in turn may reinforce the adipogenic effect of sewage feeding.

New Mutations in NEB Gene Discovered by Targeted Next-Generation Sequencing in Nemaline Myopathy Italian Patients - Daniela Piga; Francesca Magri; Dario Ronchi; Stefania Corti; Denise Cassandrini; Eugenio Mercuri; Giorgio Tasca; Enrico Bertini; Fabiana Fattori; Antonio Toscano; Sonia Messina; Isabella Moroni; et al. (Journal of Molecular Neuroscience, 2016)

Sun‐induced fluorescence – a new probe of photosynthesis: First maps from the imaging spectrometer HyPlant - U. Rascher; L. Alonso; A. Burkart; C. Cilia; S. Cogliati; R. Colombo; A. Damm; M. Drusch; L. Guanter; J. Hanus; T. Hyvärinen; T. Julitta; et al. (Global Change Biology, 2015)
Variations in photosynthesis still cause substantial uncertainties in predicting photosynthetic CO 2 uptake rates and monitoring plant stress. Changes in actual photosynthesis that are not related to greenness of vegetation are difficult to measure by reflectance based optical remote sensing techniques. Several activities are underway to evaluate the sun‐induced fluorescence signal on the ground and on a coarse spatial scale using space‐borne imaging spectrometers. Intermediate‐scale observations using airborne‐based imaging spectroscopy, which are critical to bridge the existing gap between small‐scale field studies and global observations, are still insufficient. Here we present the first validated maps of sun‐induced fluorescence in that critical, intermediate spatial resolution, employing the novel airborne imaging spectrometer HyPlant . HyPlant has an unprecedented spectral resolution, which allows for the first time quantifying sun‐induced fluorescence fluxes in physical units according to the Fraunhofer Line Depth Principle that exploits solar and atmospheric absorption bands. Maps of sun‐induced fluorescence show a large spatial variability between different vegetation types, which complement classical remote sensing approaches. Different crop types largely differ in emitting fluorescence that additionally changes within the seasonal cycle and thus may be related to the seasonal activation and deactivation of the photosynthetic machinery. We argue that sun‐induced fluorescence emission is related to two processes: (i) the total absorbed radiation by photosynthetically active chlorophyll; and (ii) the functional status of actual photosynthesis and vegetation stress.

Models to predict the start of the airborne pollen season - Consolata Siniscalco; Rosanna Caramiello; Mirco Migliavacca; Lorenzo Busetto; Luca Mercalli; Roberto Colombo; Andrew D. Richardson (International Journal of Biometeorology, 2015)

Continuous streamflow simulation for index flood estimation in an Alpine basin of northern Italy - G. Ravazzani; D. Bocchiola; B. Groppelli; A. Soncini; M.C. Rulli; F. Colombo; M. Mancini; R. Rosso (Hydrological Sciences Journal, 2015)

Direct numerical simulation of fully saturated flow in natural porous media at the pore scale: a comparison of three computational systems - M. Siena; J. D. Hyman; M. Riva; A. Guadagnini; C. L. Winter; P. K. Smolarkiewicz; P. Gouze; S. Sadhukhan; F. Inzoli; G. Guédon; E. Colombo (Computational Geosciences, 2015)

Performance of Bemisia tabaci (Genn.) Biotype B (Hemiptera: Aleyrodidae) on Weeds - L D M Sottoriva; A L Lourenção; C A Colombo (Neotropical Entomology, 2014)

ER Reorganization is Remarkably Induced in COS-7 Cells Accumulating Transmembrane Protein Receptors Not Competent for Export from the Endoplasmic Reticulum - Massimo D’Agostino; Arianna Crespi; Elena Polishchuk; Serena Generoso; Gianluca Martire; Sara Francesca Colombo; Stefano Bonatti (The Journal of Membrane Biology, 2014)

Migratory behaviour of a dominant detritivorous fish Prochilodus lineatus evaluated by multivariate biochemical and pollutant data - E. D. Speranza; N. Cappelletti; M. C. Migoya; L. M. Tatone; J. C. Colombo (Journal of Fish Biology, 2012)
This paper studies the migration pathways and ranges of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Río de la Plata basin using multivariate analysis of biochemical and pollutant data. Biochemical composition (water, ash, lipids, proteins, carbohydrates, neutral lipids classes and fatty acids), aliphatic hydrocarbons (ALI), polychlorinated biphenyls (PCB), linear alkylbenzenes (LAB) and organochlorine pesticides (OClP) were determined in muscle samples of P. lineatus collected in Metropolitan Buenos Aires, the lower Paraná River (Paraná: 200–1000 km from Buenos Aires) and the middle Paraná and Paraguay Rivers (North: 1000–1400 km north). Biochemical variables and pollutants exhibited large variability [Lipids 1·1–89·5% wet mass; ALI 1·4–413; LABs not detectable (n.d.)–115·2; PCBs n.d.–27·9; OClPs n.d.–11·8 µg g −1 dry mass], due to the contrast of Buenos Aires with North fish. Fish from Buenos Aires were fatty (lipids 24·7 ± 12·3% wet mass), enriched in 18 carbon fatty acids and severely contaminated (ALI 152·4 ± 72·3; LABs 65·1 ± 26·4; PCBs 15·2 ± 6·8; OClPs 1·8 ± 1·9 µg g −1 dry mass mean ± s.d .). In contrast, fish from North were lean (4·1 ± 3·1% wet mass), enriched in long chain (>20 carbons) polyunsaturated fatty acids, with average one to two orders of magnitude lower pollutant levels (ALI 41·2 ± 51·9; PCBs 2·2 ± 3·5; LABs 8·8 ± 21·1; OClPs 0·67 ± 0·75 µg g −1 dry mass mean ± s.d .). Paraná showed intermediate values in all variables, denoting the mixing of different fish stocks. Based on principal component analysis, 14 outliers from 60 North and Paraná samples (representing 26 from 108 individual fish) were identified as pertaining to the Buenos Aires group with very similar lipid and pollutant levels. Data suggest that P. lineatus migrates a highly variable distance, exceeding 800–1000 km in multiple spatial and temporal overlapping ranges. Chemometric analysis of biochemical and pollutant data effectively discriminates fish according to the chemical signature acquired by detritus feeding in pristine and contaminated urban or industrial areas.

With time on our side? Task-dependent compensatory processes in graceful aging - M. Berlingeri; G. Bottini; L. Danelli; F. Ferri; D. Traficante; L. Sacheli; N. Colombo; M. Sberna; R. Sterzi; G. Scialfa; E. Paulesu (Experimental Brain Research, 2010)

Ecological portrayal of old‐growth forests and persistent woodlands in the Cilento and Vallo di Diano National Park (southern Italy) - M. Marchetti; R. Tognetti; F. Lombardi; U. Chiavetta; G. Palumbo; M. Sellitto; C. Colombo; P. Iovieno; A. Alfani; D. Baldantoni; A. Barbati; B. Ferrari; et al. (Plant Biosystems, 2010)

3-D distribution of nongeniculate corallinales: a case study from a reef crest of South Sinai (Red Sea, Egypt) - A. Caragnano; F. Colombo; G. Rodondi; D. Basso (Coral Reefs, 2009)

Biochemical composition of a dominant detritivorous fish Prochilodus lineatus along pollution gradients in the Paraná‐Río de la Plata Basin - E. D. Speranza; J. C. Colombo (Journal of Fish Biology, 2009)
The biochemical composition of muscle, liver and stomach contents of a detritivorous fish Prochilodus lineatus was analysed and compared to settling particles and sediments along pollution gradients over 1500 km of the Río de la Plata Basin to evaluate the effects of anthropogenic discharges in a detritus food chain. The stomach contents of P. lineatus collected in the polluted Metropolitan Buenos Aires coast were enriched in proteins, carbohydrates and lipids, similar to settling particulates collected in the sewer area, and two to five times higher than underlying sediments, supporting the interpretation that P. lineatus feeds on unconsolidated organic flocs freshly decanted from mixed industrial and sewage outfalls. Fish from Buenos Aires had consistently higher standard length ( L S ) and mass ( M T ) slopes ( b = 3·5), condition indexes ( K = 3·01 ± 0·47, mean ± s.d .) and muscle fat content (fat = 23·8 ± 13·8% wet mass, mean ± s.d .) relative to northern fish ( b = 2·7, K = 2·22 ± 0·39, fat = 3·4 ± 3·2% wet mass, respectively), suggesting that sewage‐derived organic matter was an enriched diet, which allowed an enhanced body mass gain and fat accumulation compared to organic‐poor vegetal detritus in the north Paraná area. Buenos Aires fish also showed higher hepato‐somatic indices (mean ± s.d . I H 1·41 ± 0·49 v. 0·70 ± 0·32, respectively), which correlated with their two to three orders of magnitude higher hydrocarbon and polychlorinated biphenyl (PCB) loads, suggesting an enhanced detoxifying metabolism. The northward migration of fatty P. lineatus was evidenced by the presence of clear outliers in the L S and M T relationship, K and fat content along the Paraná River.

Acoustic survey of a jellyfish-dominated ecosystem (Mljet Island, Croatia) - G. Alvarez Colombo; A. Benović; A. Malej; D. Lučić; T. Makovec; V. Onofri; M. Acha; A. Madirolas; H. Mianzan (Hydrobiologia, 2009)

Influence of vestibular and visual stimulation on split-belt walking - B. Marques; G. Colombo; R. Müller; M. R. Dürsteler; V. Dietz; D. Straumann (Experimental Brain Research, 2007)

Cost-effectiveness of pneumococcal vaccination for prevention of invasive pneumococcal disease in the elderly: an update for 10 Western European countries - S. M. A. A. Evers; A. J. H. A. Ament; G. L. Colombo; H. B. Konradsen; R. R. Reinert; D. Sauerland; K. Wittrup-Jensen; C. Loiseau; D. S. Fedson (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Association Between the cfxA Gene and Transposon Tn4555 in Bacteroides distasonis Strains and Other Bacteroides Species - Livia Q. Ferreira; Katia E. S. Avelar; Jessica M. B. D. Vieira; Geraldo R. de Paula; Ana P. V. Colombo; Regina M. C. P. Domingues; Maria C. S. Ferreira (Current Microbiology, 2007)